The India Infrastructure Report Policy Imperatives for Growth and Welfare - Planning Commission (Planning Commission, 1996)
The new economic policies of Government of India have significant implications for different sectors of the economy, especially the urban sector. where most of the new investments are expected to be made. The likely increase in urban productivity and population will place a heavy demand on all kinds of urban infrastructure and services. Conversely. Infrastructure bottlenecks are likely to pose serious impediments in enhancing urban productivity.
Expert Group on the Commercialisation of Infrastructure Projects
Expert Group on the Commercialisation of Infrastructure Projects